Organoleptic Test of Swivel Matoa (Pometia pinnata) Ice Cream - Fajar Irianto; Anisa Tri Hutami (Formosa Journal of Multidisciplinary Research, 2022)
Matoa fruit (Pometia pinnata) is a typical Papuan fruit, which has a unique refreshing taste. In addition, the high content of vitamins C and E, can ward off free radicals and increase endurance. In this study, matoa fruit is used as an swivel ice cream flavor enhancer, which is expected to be an alternative utilization of Papua's local food diversity. The method used was making matoa ice cream with the  variation of percentage addition for matoa, which are 26%, 34.5% and 48.7%. The results obtained from the ranking test is the asymp value. Sig > 0.05 so it can be concluded that there was no significant difference between the three samples according to the panelists. In the scoring test, it was found that the p value < 0.05 on the taste and aroma parameters (there was a significant difference), but on the color and texture parameters, the p value > 0.05, so it can be concluded that there is no significant difference in the parameters of texture and color.